2014
DOI: 10.1080/09540121.2014.907385
|View full text |Cite
|
Sign up to set email alerts
|

Multiple discriminations experienced by people living with HIV in France: results from the ANRS-Vespa2 study

Abstract: Since the advent of AIDS, discrimination has remained at the core of the experience of people living with HIV (PLHIV). PLHIV who belong to minority groups are exposed to discrimination not only on the grounds of their HIV infection but also because of rejecting attitudes towards drug users, homosexuals and black people. This article aimed to measure the frequency of discrimination and assess its correlates among PLHIV in France. We used data from a national representative survey, the ANRS-Vespa2 study, conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 26 publications
3
46
0
Order By: Relevance
“…The already widely recognized benefits of early introduction of antiretroviral therapy 18 seem to be neglected by the stigma and fear of being positive 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The already widely recognized benefits of early introduction of antiretroviral therapy 18 seem to be neglected by the stigma and fear of being positive 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The BED-CEIA test was used to estimate the HIV incidence in several countries and different epidemiologic scenarios 5 , 8 , 16 , including between the reported cases of HIV to estimate the HIV incidence in the United States of America (USA) 10 .…”
Section: Introductionmentioning
confidence: 99%
“…One study reported that over two-thirds of PLWH reported that they were not allowed to go to a medical appointment during working hours without losing payment, which might be considered as stigma [26]. Another study reported that 24% of their participants indicated facing discrimination when applying for a job [31]. One study made an analysis of the complaints submitted to the Equal Employment Opportunity Commission about discrimination at work because of a chronic disease (including HIV): of all complaints filed by people with disabilities under the employment provisions of the Americans with Disabilities Act in the period 1992-2003, 7.3% concerned discrimination of PLWH.…”
Section: Level Of Perceived Stigmamentioning
confidence: 99%
“…stigma Older people, men who have sex with men, drug users, and migrant women experienced significantly more discrimination [31]. A comparative study of PLWH in different geographical regions concluded that work-related stigma and discrimination appeared more often and was more severe in the Caribbean area than in the UK [30].…”
Section: Background Characteristics Related Tomentioning
confidence: 99%
See 1 more Smart Citation